On recoverable behavior of PBTI in AlGaN/GaN MOS-HEMT. (June 2017) - Acurio, E.; Crupi, F.; Magnone, P.; Trojman, L.; Meneghesso, G.; Iucolano, F.
Highlights: Recoverable PBTI in a recessed AlGaN/GaN MOS-HEMT under different stress conditions. Universal decreasing PBTI behavior independent on stress time, voltage, and sample. Empirical recovery model with 2 time constants, which are stress voltage independent. Abstract: This experimental study focuses on the positive bias temperature instability (PBTI) in a fully recessed-gate AlGaN/GaN MOS-HEMT. A positive stress voltage to the gate results in positive threshold voltage shift (ΔVth ), which is attributed to the trapping of electrons from the GaN layer into the pre-existing oxide traps. The trapping rate exhibits a universal decreasing behavior as a function of the number of filled traps, independently of stress time, stress voltage, stress temperature, and device-to-device variability. The stress-induced ΔVth can be fully recovered by applying a small negative voltage, which causes the electron de-trapping. In the explored time window (between 1 s and thousands of s), the recovery dynamics is well described by the superimposition of two exponential functions associated with two different traps. Both trap time constants are independent of the stress voltage, decrease with temperature and increase with the recovery voltage. The activation energy of the slower trap is 0.93 eV, while the faster trap exhibits an activation energy with a large spread in the range between 0.45 eV and 0.82 eV.